MINERALIZATION AND DEFORMATION OF THE MALANJKHAND TERRANE (2,490–2,440 MA) ALONG THE SOUTHERN MARGIN OF THE CENTRAL INDIAN TECTONIC ZONE - Stein H.; Hannah Ju.; Zimmerman A.; Markey R. (My University, 2006)
The Malanjkhand Cu–Mo–Au deposit, located near the northwest margin of the Malanjkhand batholith (terrane), is a strategic and significant porphyry-style deposit that experienced a protracted 50 m.y. deformational history shortly after its formation at 2,490±8 Ma (Stein et al. 2004). In a recent study, Panigrahi et al. (2004) averaged U–Pb SHRIMP zircon data from a pooled set of samples from the Malanjkhand batholith to advocate a meaningless intermediate age of ~2,476 Ma for the Malanjkhand granitoid and its Cu–Mo–Au deposit. In the northwest part of the Malanjkhand batholith, Re–Os dating of occurrence-specific molybdenite captures not only the age of porphyry-style mineralization and associated magmatism, but also elucidates a complex deformational history that extends to ~2,450 Ma. In the central part of the Malanjkhand batholith, Re–Os dating of delicate spindles of accessory molybdenite occurring with pristine muscovite in miarolitic cavities within the undeformed microgranitoid at the Devgaon Mo prospect unequivocally shows that deformation ceased at this location no later than 2,470–2,465 Ma. The deformational history recorded at the Malanjkhand deposit in the northwest most likely reflects prolonged transpressive convergence and docking of the Malanjkhand terrane with units in the poorly understood (proto) Central Indian Tectonic Zone (CITZ) along its southern margin, the Central Indian shear zone. The timing for this convergence is Late Archean–Early Paleoproterozoic.
Keywords: MALANJKHAND; DEVGAON; RE-OS DATING; MOLYBDENITE; DEFORMATION; CENTRAL INDIAN TECTONIC ZONE; Archean; Paleoproterozoic; Precambrian::Archean; Докембрий::Архей; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская